Experimental study of the influence of changes in load direction on the performance of a crown bearing - Costa, Lucrécio (2001)
Laboratory tests have been carried out in order to investigate the influence of small changes in load direction on the performance of a steadily loaded hydrodynamic crown journal bearing. Hydrodynamic pressures, temperature distribution on the bush internal surface, shaft temperature, oil flow rate and bush torque were measured for fixed sets of operating conditions, at three different groove locations (4>) with respect to the line of load (4> = 0, -30, and +30 degrees). For each groove location quantitative information is provided concerning to the influence of applied load and shaft rotational speed on the performance characteristics. Changing the location of the groove around theload line did affect flow rate, bush torque and maximum hydrodynamic pressure, but only had a slight effect on bush maximum temperature.